Cultivating the Spirit of Servant Leadership in Christian Teachers through Technology-Based Teacher Performance Appraisals: Preliminary Studies at Christian Schools in Jakarta - Oki Hermawati; Richard; Hema Sagaro Setiawan (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The Servant Leadership (SL) model is a leadership model that is applied in the context of a Christian school. Efforts to develop the spirit of Servant Leadership integrated into the technology-based Teacher Performance Appraisal (TPA) become an interesting study to be studied further. The method used in this research is a case study where the participants involved are in the Christian school community in Jakarta. The literature review is used to see a series of efforts to develop the spirit of Servant Leadership in each teacher's personality, which is measured through a technology-based Teacher Performance Appraisal. The results of efforts to develop the leadership model of Servant Leadership will strengthen the application of the spirit of Servant Leadership in every teacher in Christian schools.